Pembelajaran Mufrodat dengan Media Wordwall Menggunakan Metode Kooperatif Learning di Kelas 4 Digital MIN 2 Palembang - Br Sinaga, Sahnila; Wasila; Irmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mastery of Arabic vocabulary (mufrodat) among fourth-grade digital students at Madrasah Ibtidaiyah Negeri 2 Palembang due to conventional memorization-based learning that tended to reduce students’ motivation and engagement. This study aimed to describe the learning process of mufrodat before and after the implementation of Wordwall media integrated with the Cooperative Learning method and to analyze its effectiveness in improving students’ learning outcomes. This research employed a mixed-method approach by combining qualitative and quantitative data. The participants were 27 students of class IV Digital B selected through purposive sampling. Data were collected through observation, interviews, documentation, and pre-test and post-test. Quantitative data were analyzed using a paired sample t-test after meeting normality and homogeneity assumptions, while qualitative data were analyzed descriptively. The results indicated a significant improvement in students’ vocabulary mastery, with the mean score increasing from 61.41 in the pre-test to 85.12 in the post-test. The paired sample t-test showed a significance value of 0.000 < 0.05, meaning that the alternative hypothesis (H₁) was accepted, which indicates that the use of Wordwall media combined with the Cooperative Learning method has a significant effect on students’ Arabic vocabulary mastery. The N-Gain score reached 56.12%, categorized as effective. These findings demonstrate that Wordwall-based Cooperative Learning is effective in enhancing students’ learning outcomes, motivation, participation, and engagement in Arabic language learning.